Minimum Acceptable Diet and its Associated Factors among Children Aged 6–23 Months in Indonesia - Pranita, Rani Fitri; Briawan, Dodik; Ekayanti, Ikeu; Triwinarto, Agus (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to assess the fulfillment of the Minimum Dietary Diversity for children (MDD), the Minimum Meal Frequency (MMF), and the Minimum Acceptable Diet (MAD) and analyze the correlation between individual, socioeconomic, and demographic characteristics and the MAD in children between the ages of 6 and 23 months in Indonesia. This study used a cross-sectional study design. The subjects were 798 children between the ages of 6 and 23 months in Indonesia from a National Total Diet Study. The data collection on the MDD, the MMF, and the MAD used twenty-four-hour dietary recall. The chi-square and multiple logistic regression models were applied in this study with a p-value<0.05 considered significant predictors of outcome variables. The MDD, MMF, and MAD were met by 63.9%, 91.3%, and 61.8% of children, respectively. Significant positive relationships of child's age, mother's educational status, and area of residence (p<0.001) to the MAD. The determinants factors of MAD were the child's age (p<0.05; OR=7.06; 95% CI:3.46–14.38) and area of residence (p<0.05; OR=1.61; 95% CI:1.19–2.15). In conclusion, it is still necessary to improve the fulfillment of the MAD (a combined indicator of the MDD and the MMF). The government's role is to provide balanced nutritional child feeding programs based on local food, strengthen behavior change communication to meet nutritionally balanced complementary foods for children, and improve child nutrition services at posyandu.